Beyond business as usual: how (and why) the habit discontinuity hypothesis can inform SME engagement in environmental sustainability practices. Issue 4 (1st October 2016) - Redmond, Janice; Wolfram Cox, Julie; Curtis, Jim; Kirk-Brown, Andrea; Walker, Beth
ABSTRACT: A lack of small and medium enterprise (SME) engagement in environmental practices has caused stakeholders to advocate several different approaches to encourage organisational change. While program investment and research has been dedicated to developing and implementing external drivers, at least two internal factors have not been given sufficient research attention when it comes to the uptake of environmental initiatives among SMEs. These are: the strength of embedded habits and routines, and whether or not a business is indeed ready to embrace change. We take these factors into account and show how a habit discontinuity approach with an emphasis on timing may foster greater engagement and uptake of environmental initiatives among SMEs. Alternatives and limitations are considered and a conceptual framework is introduced to guide research and future interventions.